Improving student asking skills through the cooperative learning model - Lesy Luzyawati; Iqna Amaliyah; Lissa Lissa; Erti Wiyati (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2023)
The purpose of this study was to confirm the model cooperative learning on the student’s questioning ability on plant world (Plantae) material. This research is a classroom action research (PTK) in SMA Negeri 1 Lohbener. Subject in this research is class X MIPA 1 with total 29 student. Instrumen in this research is observation sheet to assess questioning quality students based on Taksonomi Bloom Revisi. The results processing data the students questioning ability obtaining, first cycle as many 20 items questioning with cognitive dimension the reach C1 with precentage 65% and C2 with precentage 35%, second cycle as many 9 items questioning with cognitive dimension the reach C1 with precentage 33% and C2 with precentage 67%, and third cycle as many 17 items questioning with cognitive dimension the reach C1 with precentage 6%, C2 with precentage 88%, and C3 with precentage 6%. From obtaining data it was concluded that the quality questioning students have not achieved success, because obtain to succcess if quality questioning reach cognitive dimension C6.